The academic benefits of 'letting go': the contribution of mindfulness and nonattachment to adaptability, engagement, and grades. Issue 6 (3rd July 2019) - Elphinstone, B.; Whitehead, R.; Tinker, S. P.; Bates, G.
Abstract: Previous research has indicated that nonattachment mediates the relationship between mindfulness and the ability to be adaptable. Additionally, adaptability has been associated with increased academic engagement and subsequently, higher grades. The current study combined these findings into a single model. In an undergraduate sample ( N = 725), the results indicated that mindfulness and nonattachment were directly associated with greater adaptability and engagement. Increased adaptability was also directly associated with increased engagement, and engagement was associated with higher grades. Therefore, mindfulness and nonattachment were also found to be indirectly associated, albeit weakly, with higher grades. The current findings, therefore, add to the literature by indicating that mindfulness and nonattachment are both worthy of consideration in future research on student outcomes.